2009
DOI: 10.1029/2007wr006665
|View full text |Cite
|
Sign up to set email alerts
|

Responses of streamflow to climate and land surface change in the headwaters of the Yellow River Basin

Abstract: [1] The headwater catchments of the Yellow River Basin are of great importance for the whole basin in terms of water resources, and streamflow from these catchments has decreased in the last decades. The concept of climate elasticity was used to assess the impacts of climate and land surface change on the streamflow. Results show that for the period 1960-2000 the elasticity of streamflow in relation to precipitation and potential evapotranspiration are 2.10 and À1.04, respectively, indicating that streamflow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
334
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 392 publications
(357 citation statements)
references
References 26 publications
9
334
0
6
Order By: Relevance
“…Prior studies [23,27,43] have proposed nonparametric approaches to estimate e x from observed climatic data. Of the various approaches (Table S2, Figure S2) found in the literature, we have no reason to favor one over the others, and thus use the average of e p estimated from all available non-parametric approaches to predict average changes in Q under the alternative LULC scenario.…”
Section: Climate Elasticity Of Streamflow and Changes In Streamflowmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies [23,27,43] have proposed nonparametric approaches to estimate e x from observed climatic data. Of the various approaches (Table S2, Figure S2) found in the literature, we have no reason to favor one over the others, and thus use the average of e p estimated from all available non-parametric approaches to predict average changes in Q under the alternative LULC scenario.…”
Section: Climate Elasticity Of Streamflow and Changes In Streamflowmentioning
confidence: 99%
“…To compute e x estimates from the historic climate record, we used PET instead of ET similar to prior studies [22][23] due to data limitations associated with the estimation of actual ET from 1950-2009. Further, as e pet was computed using historic PET estimates, we used PET instead of ET from the regional climate model simulations to estimate changes in Q to maintain consistency in the methodology.…”
Section: Climate Elasticity Of Streamflow and Changes In Streamflowmentioning
confidence: 99%
See 3 more Smart Citations